Zinc and Trimethylsilyl Chloride Mediated Synthesis of 2,3,5-Trisubstituted Pyrrole Diesters from Nitriles and Ethyl Bromoacetate - Rao, H. Surya Prakash; Desai, Avinash (Synlett, 2015)
An efficient, zinc-mediated, single-pot and CN+3C type pseudo-four-component synthesis of 2,3,5-trisubstituted pyrrole diesters was achieved from readily available aromatic/benzylic/aliphatic nitriles and ethyl bromoacetate under trimethylsilyl chloride catalysis.
Keywords: Blaise reaction; pyrroles; tandem processes; pseudo four component